Pelatihan Aplikasi Yhomework-Math Solver untuk Meningkatkan Kemampuan Belajar Matematika Siswa SDN Gunung Pasir Jaya selama Pembelajaran dari Rumah - Saputri, Maria Edistianda Eka; Oktarin, Irene Brainnita (Universitas Nusantara PGRI Kediri, 2022)
Early 2020 the Covid-19 pandemic broke out everywhere, this resulted in the Kemdikbud issuing a home learning program through online learning where all students were not allowed to study in school as before. SDN Gunung Pasir Jaya, which is an implementation of the circular given by Kemdikbud for learning from home. This makes the delivery of subject matter and the interaction between teachers and students less than optimal. Some children have difficulty understanding the material, sepecially in Mathematics. In order to help students reduce the difficulty of understanding the material in Mathematics, independent learning application training for Mathematics subject is provided. The implementation of activities is carried out in several stages, namely preparation, teaching, training, and evaluation. The PKM activity of the independent learning application for students of SDN Gunung Pasir Jaya has a positive influence on students and teachers alike; and overall, this activity provides knowledge about the use of the Yhomework-Math Solver application as a learning media solution during the teaching and learning process at home.